(untitled) (International Journal of Studies in Nursing, 2018)
Background: Quality of family planning services is an ever-increasing worldwide issue which is basically deserted in the developing nations. Provision of high quality family planning services that satisfy clients’ needs can ensure continued services utilization and increase contraceptive prevalence rate, lowered fertility rate, and improved women and children’s health. Aim: this study intended to assess the quality of family planning services in maternal and child health care centers in Damanhour city. Design: this was a descriptive study that utilized Dounabedian model to assess quality of family planning services structure and process and clients’ satisfaction was used as an outcome indicator. Setting: the three available maternal and child health centers in Damanhour city. Participants: all health care providers and a convenience sample of 300 non pregnant women who utilized the family planning clinics at the selected maternal and child health centers. Tools of data collection: three tools were utilized; basic data structured interview schedule for clients and health care providers, structural quality is assessed through facility audit while the process of family planning services provision was measured by using an observational checklist. After the observation of the family planning care process, an exit interview was done with the clients to measure their satisfaction with the provided family planning services. Results: The study findings revealed that none of the studied family planning clinics had high total quality of care level (structure & process) where 66.7% of them had low level of the total quality of care. However, 74.3% of the studied family planning clients were moderately satisfied with the total quality of care level (structure & process) in the studied maternal and child health centers. Finally, a significant positive correlation was confirmed between the overall family planning clients’ satisfaction level and the total quality of family planning care level; total structure and total process quality of family planning services delivery. Conclusion and recommendations: it can be concluded that family planning services in maternal and child health centers at Damanhur had low total quality of care level with moderate clients’ satisfaction. This shed the light on the urgent need for numerous quality enhancement measures to promote all quality elements in the studied maternal and child health centers. In addition to, emphasizing clients’ satisfaction as a high priority output of care.